2011
DOI: 10.1038/aps.2011.44
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ryanodine receptors for anti-arrhythmic therapy

Abstract: Antiarrhythmic drugs are a group of pharmaceuticals that suppress or prevent abnormal heart rhythms, which are often associated with substantial morbidity and mortality. Current antiarrhythmic drugs that typically target plasma membrane ion channels have limited clinical success and in some cases have been described as being pro-arrhythmic. However, recent studies suggest that pathological release of calcium (Ca 2+ ) from the sarcoplasmic reticulum via cardiac ryanodine receptors (RyR2) could represent a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 76 publications
(102 reference statements)
0
31
0
Order By: Relevance
“…We will focus only on the role of RyR2-phosphorylation in CPVT, and refer the reader to prior reviews about other aspects of CPVT including the potential role of reduced FKBP12.6-binding and domain-unzipping as mechanisms of RyR2-destabilization. 62, 64 …”
Section: Role Of Ryr2-phosphorylation In Ventricular Arrhythmogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…We will focus only on the role of RyR2-phosphorylation in CPVT, and refer the reader to prior reviews about other aspects of CPVT including the potential role of reduced FKBP12.6-binding and domain-unzipping as mechanisms of RyR2-destabilization. 62, 64 …”
Section: Role Of Ryr2-phosphorylation In Ventricular Arrhythmogenesismentioning
confidence: 99%
“…64 Several studies have shown that RyR2-phosphorylation uncovers latent single-channel dysfunction of mutant RyR2. 6567 Other studies have shown that only SR Ca2+ overload, without activation of PKA, can unmask the ‘gain-of-function’ phenotype of CPVT-mutant RyR2 variants.…”
Section: Role Of Ryr2-phosphorylation In Ventricular Arrhythmogenesismentioning
confidence: 99%
“…This was demonstrated again more recently by the use of RyR2 block by carvedilol and its derivatives, which prevented stress-induced ventricular tachyarrhythmias in RyR2-mutant mice (Zhou et al, 2011). However, previous attempts to use RyR2 inhibitors to reverse effects of RyR2 mutations have not been successful in preventing arrhythmia (reviewed by McCauley and Wehrens, 2011;Watanabe and Knollmann, 2011). For example, the dual Na 1 and RyR2 antagonist tetracaine did not suppress the Ca 21 waves in CASQ2…”
Section: Introductionmentioning
confidence: 99%
“…This natural diterpene from the South American plant Ryana speciosa Vahl was originally identified as the hydrolysis product of ryanodine, a compound that alters the function of an intracellular calcium channel known as the ryanodine receptor, and a natural product that has been used as a tool to understand the role that intracellular Ca 2+ channels play in biology. 1 Over the past two decades, structure–activity relationships associated with ryanodine, ryanodol, and synthetic esters of ryanodol/ryanodine have led to the conclusion that a wide variety of ryanoids have diverse and potent effects on Ca 2+ channels in vivo , despite the wide range of binding affinities reported for them. 1a From a chemical standpoint, ryanodine and ryanodol first stood as complex problems for structure elucidation due, in part, to the great number of fully substituted carbon atoms in their complex polycyclic skeletons.…”
mentioning
confidence: 99%